A Non-Parametric Analysis of Productivity: The Case of U.S. and Japanese Manufacturing - Chavas, Jean-Paul; Cox, Thomas L. (American Economic Review, 1990)
A non-parametric analysis of technology, technical change, and productivity is presented in the context of cost minimizing behavior. A number of non-parametric tests concerning the existence and nature of technical change are applied to U.S. and Japanese manufacturing data. Non-parametric measures of technical change are presented.